The use of value clarification technique-based- picture story media as an alternative media to value education in primary school (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2017)
Developing learning media by adjusting it to the subject materials’ characteristics and students’ development needs to be done. Based on this concern, this research is aiming at developing picture story media that is based on value clarification technique (VCT) as an alternative value education in primary school. This research employed Research and Development (R D) study approach and specifically adapted the study model from Dick and Carey (2001). Data collection was done through documentation note, observation, questionnaire, and try out. Data that had been collected then was analysed by using qualitative and quantitative methods (mix methods). Based on the try out result, it shows that the picture story media that is being developed has fulfilled the criteria of validity, effectivity, and practicality. Besides, based on the observation results of the tests’ try out process, it shows that the media has given positive impact towards the expected learning process and results.